[SPS seminar on identity - 18 June 2011] - Chronology 1970-2000. - Stampa, Pietro (Rivista di Psicologia Clinica, 2011)
We propose a commentary on the chronology of critical events in a cultural and political sense during the three decades 1970-2000, with special reference to the need to position the development of Italian psychology correctly in the history of the country.The subdivision into decades is a mere convention and is done for ease of consultation.